Zinc oxide–chitosan dressing for grade IV pressure ulcers post-debridement with complications: A case report - Putri Noor Kholisoh Purnama Wati; Nursiswati; Hasniatisari Harun (The Journal of Palembang Nursing Studies, 2024)
Background: Pressure ulcers require appropriate management to prevent complications and reduce mortality. Several factors can delay wound healing, including diabetes mellitus, malignancies, inadequate nutrition, hypoalbuminemia, anemia, and immobility. Therefore, selecting the appropriate wound dressing is crucial. Zinc oxide and chitosan dressings have been shown to enhance wound healing and promote tissue epithelialization.Objective: To evaluate the outcomes of zinc oxide and chitosan dressing application in a patient with a grade IV pressure ulcer following surgical debridement and presenting with multiple complicating factors.Case: This case study involved the application of zinc oxide and chitosan dressings in a patient with a grade IV pressure ulcer post-surgical debridement. During the first month, the treatment was combined with antimicrobial dressings. Dressings were changed every 2 to 3 days. Ulcer severity was assessed using the National Pressure Ulcer Advisory Panel criteria, and healing progress was measured with the Pressure Ulcer Scale for Healing.Conclusion: The pressure ulcer showed progressive improvement over 8 months. However, complete healing was not achieved due to several complicating factors that delayed the healing process, including comorbidities, immobility, inadequate nutrition, urinary catheter use, the severity of the ulcer, anemia, and hypoalbuminemia